Magnum Opus of Mohammed Arkoun; Cultural Resilience Amidst Pluralism - Sigit Tri Utomo; Marhumah Marhumah; Karwadi Karwadi; Mohamad Ardin Suwandi (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
The world faces a multidimensional crisis, with cultural, ethnic, racial, linguistic, and ethnic diversity giving rise to various issues. Wars in different parts of the world continue to result in bloody events and casualties. Preventive efforts are needed to address these problems, including promoting a culture of tolerance. Mohammed Arkoun was a figure and philosopher of pluralism who advocated and conveyed ideas about pluralism. The weaknesses of classical Islamic theological thinking become apparent when confronted with the empirical social reality of human life that continues to evolve with the advancement of science and technology. Mohammed Arkoun, an intellectual fNrom Algeria, attempted to comprehensively reinterpret the framework of Islamic thought, including aspects such as theology (kalam), Sufism, jurisprudence (fiqh), ethics, and exegesis (tafsir). Mohammed Arkoun expressed that Islam can succeed if Muslims adopt an open attitude toward pluralistic thinking, as during the early Islamic period and the Middle Ages. This pluralism can be realized if religious understanding is based on human values, allowing Muslims to interact with anyone. This research uses a qualitative method with a literature review study type, gathering data from various references, books, and articles related to Mohammed Arkoun's magnum opus: the study of cultural tolerance resilience amid pluralism. According to Arkoun, debates based on cultural diversity, thought, and theology in classical Islam lead to profound interpretations of the Quran and laws based on sacred texts.